Gradenigo syndrome: an unexpected otitis complication - Mendes, Catarina (2016)
Introduction: Gradenigo syndrome (also known as apical petrositis) is a clinical triad of otitis media, trigeminal neuralgia and ipsilateral abducens nerve palsy. In the era of antibiotic therapy, it is an exceptional but potentially life threatening complication of acute otitis media, requiring prompt diagnosis and treatment. Case report: A seven-year-old girl with previous history of otitis, presented with left ear pain, headache, diplopia and fever. Diagnosis of Gradenigo syndrome was established and she was treated with systemic broad-spectrum antibiotics and myringotomy with timpanostomy tube placement. Clinical outcome was favourable. Conclusion: This case documents therapeutic success and total recovery with a conservative approach in an immunocompetent child with Gradenigo syndrome.